Dharma Theory: A Critical Analysis in Four Schools of Buddhism - Borah, Bishnu; Deka, Nandini (International Journal of Psychosocial Rehabilitation, 2019)
Dharma is very important notion in Buddhisim. Dharma is that which bears (dhārana), the selfcharacteristics and common characteristics of a person. All four schools of Buddhism explain the dharma theory according to their philosophy that varies in their understanding of the concept of person. In a general sense dharma refers to the categories that constitute the physical world and the person. Thus, dharma is the means to achieve prajñā (supreme knowledge) and Nirvāna, the supreme dharma. But at the same time, extinguishing of the defilements is possible through the discernment of the dharmas. Different schools of Buddhism have given different interpretations regarding the nature of dharma and its kinds on the basis of their own philosophy. This paper intends to critically analyze the concept of dharma and its kinds in main four schools of Buddhism.